Suicide risk in depression and bipolar disorder: Do impulsiveness-aggressiveness and pharmacotherapy predict suicidal intent? - Maurizio Pompili (Dove Medical Press, 2008)
Maurizio Pompili1,2, Marco Innamorati3, Michele Raja4, Ilaria Falcone2, Giuseppe Ducci5, Gloria Angeletti2, David Lester6, Paolo Girardi2, Roberto Tatarelli2, Eleonora De Pisa21McLean Hospital, Harvard Medical School, Boston, MA, USA; 2Department of Psychiatry, Sant’Andrea Hospital, “Sapienza” University of Rome, Italy; 3Università Europea di Roma, Italy; 4Diagnostic and Therapeutic Psychiatric Services, Department of Mental Health, Santo Spirito Hospital, Rome, Italy; 5Diagnostic and Therapeutic Psychiatric Services, Department of Mental Health, San Filippo Neri Hospital, Rome, Italy; 6Center for the Study of Suicide, Blackwood, NJ, USAAbstract: The aims of the present study were to examine clinical, personality, and sociodemographic predictors of suicide risk in a sample of inpatients affected by major affective disorders. The participants were 74 inpatients affected by major depressive disorder or bipolar disorder-I. Patients completed a semi-structured interview, the Beck Hopelessness Scale, the Aggression Questionnaire, the Barratt Impulsiveness Scale, and the Hamilton scales for depression and anxiety. Over 52% of the patients were high suicide risks. Those at risk reported more severe depressive-anxious symptomatology, more impulsivity and more hostility. Impulsivity, the use of antidepressants, anxiety/somatization, and the use of mood stabilizers (a negative predictor) resulted in accurate predicting of suicide intent. Impulsivity and antidepressant use were the strongest predictors even after controlling for several sociodemographic and clinical variables.Keywords: suicide, mood disorders, pharmacotherapy, impulsiveness, aggressiveness